Analysis of Chemistry Laboratory Management at Sultan Iskandar Muda Senior High School Medan - Meilani Azizah; Rama Cahaya Situngkir; Lera Sani Damah Putri; Nurfajriani (Universitas Negeri Medan, 2026)
This study aims to describe the management of the chemistry laboratory at Sultan Iskandar Muda Private Senior High School in Medan. Using a descriptive qualitative approach through observation, interviews, and documentation, the findings reveal that laboratory management has generally met standard criteria, including well-organized layout, systematic administration, proper management of equipment and chemicals, and adequate implementation of occupational health and safety (OHS). However, several aspects such as digital-based administration, structured waste management systems, and supporting facilities still require improvement. These findings contribute to the development of integrated and standard-based chemistry laboratory management in schools, particularly by emphasizing the importance of aligning management, administration, and safety practices to enhance laboratory effectiveness and sustainability.